Microthrix parvicella에 의한 슬러지 벌킹과 거품문제 해결 - 강민기(Min Gi Kang); 김영철(Young Chul Kim); 방성호(Seong Ho Bang); 이진우(Jin Woo Lee); 하준수(Jun Su Ha) (Daehan hwan'gyeong gonghag hoeji, 2006)
This study was undertaken to control sludge bulking and foaming problems at the biological nutrient removal processes. A sewage treatment plant(STP) had a severe sludge settling problem usually over 90% in 30 min settled sludge volume and 300 mL/g in SVI and also thick and heavy brown foam in the secondary clarifiers. Identification study shows that causative filament was Microthrix parvicella which has not been previously reported in Korea. According to the inspection of processes and other related parameters, excessive growth of this particular filament was associated with high SRT caused by lack of proper capacity in sludge treatment line. After providing an extension of the sludge treatment capability, the plant can decrease SRT by wasting more sludge from the processes and also decreasing SS concentration in recycled stream. Subsequently we were able to control growth of M. parvicella. The SVI value was reduced to half of those observed during the severe bulking, but also sludge blanket and its concentration in the clarifier became compact and dense. However, decrease in population of M. parvicella caused increase of total phosphorus concentration in the effluent. 본 연구는 고도처리시설에서 발생하는 벌킹과 거품문제를 해결하기 위하여 착수하였다. 현장조사결과 $SV_{30}$값은 90%, SVI 값은 300 mL/g 이상을 보여 심각한 벌킹문제와 함께 거품문제를 겪고 있었다. 하수처리장에서 벌킹과 거품문제를 야기하는 사상체를 형태적 특성과 염색반응을 통하여 조사한 결과 그 동안 우리나라에서 보고 된 적이 없는 Microthrix parvicella와 type 0092로 동정되었고 슬러지내 사상체의 밀도로 볼 때 M. parvicella가 벌킹과 거품의 원인 사상체이었다. 문제해결을 위해 연구대상 하수처리장의 공정과 관련 인자를 면밀히 조사한 결과 슬러지 처리시설의 용량과 성능에 문제가 있는 것으로 나타났다. 탈수용량의 부족으로 인해 운전 SRT를 높게 가져갈 수밖에 없는 상황이었으며 특히 낮은 슬러지 회수율은 다량의 원인 사상체를 재순환시켜 공정내에 축적 증식시켜 문제를 더욱 악화시키는 것으로 밝혀졌다. 탈수기 용량을 확충하고 성능을 개선시킨 결과 운전 SRT를 크게 감소시킬 수 있었으며, 그 결과 SVI 값은 이전의 절반 내외로 크게 줄어 침전성이 크게 향상되었다. 아울러 벌킹제어결과 2차 침전지에서 슬러지 블랑킷 깊이도 안정되었고 그 농도도 크게 증가하였다. 그러나 M. parvicella의 증식완화는 처리수의 인 농도 상승을 가져왔다.